Abnormal pigment epithelium-derived factor processing in progressive myopia. (November 2016) - Minkevich, Natalya I.; Morozova-Roche, Ludmilla A.; Iomdina, Elena N.; Rakitina, Tatiana V.; Bogachuk, Anna P.; Kakuev, Dmitry L.; Smirnova, Evgeniya V.; Babichenko, Igor I.; Lipkin, Valery M.
Abstract: Pigment Epithelium-Derived Factor (PEDF) is a secreted glycoprotein belonging to the family of non-inhibitory serpins. It is known, that in cases of complicated myopia, the content of PEDF in aqueous humor of the anterior chamber is significantly reduced. Here we examined a bulk of Tenon's capsule samples obtained from various groups of myopes, to examine PEDF processing in progressive myopia. We have analyzed the distribution of full length PEDF50 and its truncated form PEDF45 in the soluble and insoluble fractions extracted from Tenon's capsule of myopic and control (non-myopic) patients using SDS-polyacrylamide gel electrophoresis, as well as monitored the proteolytic degradation of PEDF ex vivo by enzyme-linked immunosorbent assay. These results were complemented by PEDF mRNA analysis in correspondent tissues by using qPCR and immunohistochemistry analysis of PEDF distribution in normal and myopic specimens. We found that in the Tenon's capsule of patients suffering from a high myopia the level of "soluble" 45 kDa PEDF reduced by 2-fold, while the content of "insoluble" 50 kDa form of PEDF was increased by 4-fold compared to controls. Excessive amount of PEDF50 in myopic specimens have been shown to correlate with the abrogated PEDF processing rather than with an increase of its expression. Moreover, immunohistochemical staining of the myopic Tenon's capsule tissue sections revealed the halo of deposited PEDF50 in the fibroblast extracellular space. These findings suggest that in myopia limited proteolysis of PEDF is altered or abrogated. Accumulation of full-length PEDF insoluble aggregates in the fibroblast intercellular space may affect cell survival and consequently causes the destructive changes in the extracellular matrix of the eye connective tissues. As a result, the abrogation of full-length PEDF normal processing can be an important mechanism leading to biomechanical destabilization of the scleral capsule and myopia progression. Highlights: Amount of soluble PEDF was decreased in Tenon's capsule of myopic patients. Predominant uncleaved form of PEDF was found in Tenon's capsule of myopic patients нера≿♯епленная форма PEDF. Uncleaved PEDF accumulates as amyloid-like fibrils in the intercellular space.